Tinjauan Sistematis tentang Paparan BTEX pada Pekerja Industri Pembuatan Sepatu - Ojelabi, Azeez Olawale; Tualeka, Abdul Rohim; Paskarini, Indriati (Universitas Airlangga, 2025)
Background: Many chemicals, including volatile organic compounds (VOCs) like benzene, toluene, ethylbenzene, and xylene (BTEX), are commonly used in the shoe industry. Because of these substances’ toxicological characteristics, workers are exposed to serious health risks. Objectives: This article aims to systematically review BTEX exposure among workers in the shoe-making industry, focusing on associated health risks and the effectiveness of mitigation strategies. It explores how occupational factors such as hand hygiene, age, job type, smoking habits, and personal protective equipment usage influence the severity of BTEX exposure effects. Methods: This systematic review examined the impact of BTEX exposure on shoemaking industry workers, selecting 32 national and international articles based on keyword-based searches. Exclusion criteria included past publications, risk assessment, exposure measurement, and mitigation strategies. Inclusion criteria included publications from the past 10 years. Data extraction included BTEX exposure levels, health outcomes, and working conditions. Results: The review highlights the health risks of BTEX exposure to shoemaking workers, including leukemia, neurological impairment, respiratory problems, and reproductive issues, emphasizing the need for improved safety protocols. Conclusion: This review drew attention to the health risks that BTEX compounds pose to workers in the shoe industry, emphasizing the need for stronger safety regulations and enforcement as well as recommendations for future studies on safer procedures.